The Role Of Principal Leadership In Improving Teacher Welfare: A Case Study At Muhammadiyah Rabbani Elementary School - Khofifah Umi Rahmawati; Muhammad Munadi (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Teacher welfare is a crucial factor influencing motivation, performance, and the quality of learning. While previous research has largely discussed the relationship or influence of teacher welfare on performance, there are still limited studies explaining the forms of welfare efforts undertaken by schools, particularly in private schools. This study aims to analyze the role of principal leadership in improving teacher welfare at Muhammadiyah PK Rabbani Elementary School. This study uses a descriptive qualitative approach. The research subject is the principal as the primary source of information, while informants include teachers, employees, and educational staff. Data were collected through semi-structured interviews, participant observation, and documentation studies. Data validity was tested using triangulation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The results show that the principal plays a significant role in improving teacher welfare, both financially and non-financially. Financially, the principal lobbies and negotiates for additional incentives for teachers despite limited authority. From a non-financial perspective, the principal creates a positive work environment, provides opportunities for professional development, and provides recognition and rewards for teacher achievement. In conclusion, effective principal leadership contributes significantly to improving teacher well-being, which in turn supports the quality of education in schools.